Discrepancy in perception of bullying experiences and later internalizing and externalizing behavior: A prospective study. Issue 5 (22nd March 2017) - Hwang, Soonjo; Kim, Young Shin; Koh, Yun‐Joo; Bishop, Somer; Leventhal, Bennett L.
Abstract : Discrepancy in perception of bullying experiences may lead to later internalizing or externalizing behavior in adolescents. A 1, 663 South Korean 7th and 8th graders (mean age: 13.1 and 14.1 years old), were seen for a follow‐up study to examine the relationships between the discrepancy in perception of their bullying experiences (defined as discrepancy between self‐ and peer‐reports of bullying experiences) and internalizing or externalizing behavior at follow‐up. Bullying was assessed by self‐ and peer‐report. The discrepancy in perception of bullying experiences was defined by the concordance or discordance between self‐ and peer‐reports. Internalizing and externalizing behavior was evaluated using the Youth Self Report and Child Behavior Checklist, at baseline and follow‐up. Two by two ANCOVA was performed with a factorial design, categorizing discrepancy in perception of bullying experiences based on the agreement between self‐report and peer‐report. Internalizing/externalizing behavior‐at‐follow‐up was used as an outcome, adjusting for other known risk factors for internalizing/externalizing behavior, including baseline internalizing/externalizing behavior, and bullying experiences. Adolescents with perceptions of bullying experiences discrepant from peer‐reports showed increased internalizing/externalizing behavior at follow‐up. Bullying also stands out as an independent risk factor for the development of future externalizing behavior even among adolescents with accurate perceptions of bullying experiences. These specific groups of youth warrant more focused assessment and intervention.